If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3x + -4) = 3(12x + 2) Reorder the terms: 12(-4 + 3x) = 3(12x + 2) (-4 * 12 + 3x * 12) = 3(12x + 2) (-48 + 36x) = 3(12x + 2) Reorder the terms: -48 + 36x = 3(2 + 12x) -48 + 36x = (2 * 3 + 12x * 3) -48 + 36x = (6 + 36x) Add '-36x' to each side of the equation. -48 + 36x + -36x = 6 + 36x + -36x Combine like terms: 36x + -36x = 0 -48 + 0 = 6 + 36x + -36x -48 = 6 + 36x + -36x Combine like terms: 36x + -36x = 0 -48 = 6 + 0 -48 = 6 Solving -48 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -4x^2-9x-6=0 | | -(6x-4)=-4(x+6) | | (4+2n^3)+(5n^3+2)=0 | | -(7y+3)-(-6y-4)=-3 | | 3+3m-1=9m+6-5m | | 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s | | 5x^5=20x^3 | | 2x^2-15x+27=0 | | 4x+2*8=9*4x | | -2(7r+1)-6=-64 | | 2x^2-7x+9=x+1 | | -7.5x=15.0 | | -36=-v+8(v-8) | | 5y=10x-15 | | 162=6x+6(x+7) | | x^2-18x+70=0 | | 6x-7y=49 | | 16-6b=8-7b | | 2x+4x+3x+5=50 | | 0.3n=12 | | 2x-50+4x-63+3x+20=360 |